PENGEMBANGAN MODEL PERMAINAN BOLAPANTUL SEBAGAIMATERI PEMBELAJARAN PERMAINAN BOLAVOLIDI SEKOLAH MENENGAH PERTAMA - Ahmad Rithaudin dan Budi Prasojo (Departement of Sports Education, Faculty of Sport Sciences Yogyakarta State University, 2014)
AbstractThe research is encouraged by the problem of less optimal student learning outcomes in physical education learning,in particular on passing in volleyball materials. This study aims to develop rebound ball game as learning material inthe volleyball game. This research is developing. This research is intended to produce a particular product, and test thefeasibility of the product. The data in this study were taken by survey techniques and using instruments questionnaire.The data collection techniques were done by giving questionnaires to the material experts, the teachers, and thestudents. The subjects are three experts, one physical education teacher and 32 students who are from the secondgrade. The data analysis technique used in this research is descriptive quantitative with percentage. The results ofthis study are the models of rebound ball game that consist of four different models of the game with various levelsof difficulty. While based on the assessment results of the experts, the physical education teacher and students, itcan be concluded that the model is feasible to be used as learning material for volleyball game lower pass in physicaleducation lesson for junior high school students of second grade in junior high school.Key Words: Rebound Game, volleyball game learning, junior high schoolAbstrakPenelitian ini dilatarbelakangi oleh permasalahan kurang optimalnya hasil belajar siswa di dalam pembelajaranpendidikan jasmani, khususnya materi permainan bolavoli pada tema passing bawah. Penelitian ini bertujuan untukmengembangkan model permainan bolapantul sebagai materi permainan bolavoli dalam pembelajaran pendidikanJasmani. Penelitian ini merupakan penelitian pengembangan. Penelitian ini bertujuan untuk menghasilkan produktertentu, dan menguji kelayakan produk tersebut. Data pada penelitian ini diambil dengan teknik survei danmenggunakan instrumen kuisioner. Teknik pengumpulan data dengan memberikan angket kepada ahli materi, gurudan siswa. Subjek penelitian ini adalah 3 ahli materi, guru pendidikan jasmani dan siswa kelas VIII yang berjumlah 32orang. Teknik analisis data yang dilakukan dalam penelitian ini adalah deskriptif kuantitatif dengan persentase. Hasilpenelitian ini berupa model permainan bolapantul yang terdiri atas empat macam model permainan dengan tingkatkesulitan yang bervariasi. Sedangkan berdasar hasil penilaian dari ahli materi, guru pendidikan jasmani dan siswadapat disimpulkan bahwa model permainan bolapantul sangat layak dijadikan sebagai materi untuk pembelajaranpassing bawah permainan bolavoli dalam pembelajaran pendidikan jasmani untuk siswa SMP kelas VIII. Kata kunci: Permainan bolapantul, pembelajaran permainan bolavoli, Sekolah Menengah Pertama.